Improving Student Learning Outcomes Through the Active Knowledge Sharing Method Aided by Crossword Media - Alviani Zulfika Siallagan; Caska Caska; Mujiono Mujiono (CV. Rayyan Dwi Bharata, 2023)
This study aims to determine the increase in student learning outcomes through the Active Knowledge Sharing method, assisted by crossword puzzles in economics class XII-IPS2 SMAN 3 LANGGAM. This research is a type of Classroom Action Research (CAR). The research subjects were 24 students of class XII-IPS2 SMAN 3 LANGGAM. The data collection is done through documentation and tests. The data analysis technique was performed using the parametric statistical method, namely the Paired Sample T-Test T-Test analysis technique. The results showed that: 1) The value of tcount in the calculation of the Pre-Test value to the Post-Test value of Cycle I was -6.086 with Sig. (2-tailed) 0.000. Because the value of Sig. (2-tailed) of 0.000 0.05, this indicates that there is a significant difference between the Pre-Test value and the Post-Test value of Cycle I. 2) The tcount in the calculation of the Pre-Test value against the Post-Test value of Cycle II is - 9,853 with sig (2tailed) 0,000. Because the value of Sig. (2-tailed) of 0.000 0.05, this indicates that there is a significant difference between the Pre-Test value and the Post-Test value of Cycle II. This means that there is an increase in student learning outcomes through the Active Knowledge Sharing method, assisted by crossword puzzles in economics class XII IPS2 SMAN 3 LANGGAM.